Analysis of microbiotas between traumatic and ulcerative wound: insights into challenges of current wounds managements - Chen, Cheng; Wang, Jiao; Li, Yifei; Fan, Zhenxin; Dai, Yan (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveWounds frequently occur during daily activities and clinical treatments, exerting substantial impacts on patients’ health status and recovery processes.MethodsAll the patients were enrolled for this analysis from January 2022 to December 2022 who received wound management at Wound Care Center, West China Hospital, Sichuan University, which was a single center, prospectively designed observational study. In this investigation, microbial samples were collected from 106 traumatic wounds and 157 ulcerative wounds and analysed by 16S rRNA gene sequencing.ResultsThe findings revealed distinct differences in the microbial composition and function between traumatic and ulcerative wounds. Specifically, ulcerative wounds exhibited significantly higher abundances of infection- and pro-inflammation-related microbes, such as Corynebacterium auriscanis, Finegoldia magna, and Corynebacterium striatum, whereas traumatic wounds had a significantly elevated abundance of Bifidobacterium longum, which is known to promote wound healing.​ Regarding functional profiles, the relative abundances of lipopolysaccharide (LPS) biosynthesis, fatty acid biosynthesis, and metabolism of xenobiotics by cytochrome P450 were notably higher in the traumatic wound group. In contrast, the ulcerative wound group showed significantly greater relative abundances of drug metabolism - other enzymes, folate biosynthesis, and cysteine and methionine metabolism.ConclusionComparative analyses of the microbial communities in wounds reveled that traumatic wounds, especially non-postoperative wounds, were more easily to heal, however, the ulcerative wounds, especially the non-venous wounds, were more difficult to heal. These results suggest that different types of wounds harbor distinct microbial compositions, providing valuable data to inform improved clinical wound management strategies.